Analisis Temporal Perubahan Suhu Permukaan Tanah di Kabupaten Pati Tahun 2017 dan 2024 - Puspita Dewi, Dhyah; Adhar, Khairunnisa (Perencanaan Wilayah dan Kota, Institut Teknologi Kalimantan, 2025)
This study analyzes changes in land surface temperature (LST) in Pati Regency between 2017 and 2024 using Landsat 8 satellite data. The analysis results show a significant increase in surface temperature over the period, with the lowest temperature rising from 19°C to 21°C and the highest temperature rising from 39°C to 42°C. The temperature increase mainly occurred in the foothills of Mount Muria and the southern part of Pati Regency, likely influenced by land use changes and dry season conditions. Additionally, the Normalized Difference Vegetation Index (NDVI) analysis indicates a decrease in vegetation density in most areas, contributing to the rise in surface temperature. These findings provide crucial insights for policymakers in formulating sustainable spatial planning strategies in Pati Regency.